Validity of Method for MTBC and NTM Detection in FNAB Specimens from Tuberculous Lymphadenitis Using Microscopy, XPERT MTB / RIF and Culture Method - Junus, Herisa Nataliana; Mertaniasih, Ni Made; Soedarsono, Soedarsono (Indonesian Journal of Tropical and Infectious Disease, 2021)
Mycobacterium tuberculosis and Nontuberculous Mycobacteria usually cause infection in tuberculous lymphadenitis. To improve accuracy of the detection MTB and NTM bacteria it is necessary to select valid methods. This study aims to compare validity of diagnostic methods from FNAB specimens for determining tuberculous lymphadenitis patients. a descriptive observational laboratory study involved 35 samples were obtained from tuberculous lymphadenitis patients in Dr. Soetomo Hospital Surabaya East Java. All specimens examined Ziehl-Neelsen staining microscopy, Xpert MTB/RIF , culture method Middlebrook7H10 solid media and  MGIT as Gold standard. Identification of MTB dan NTM with SD Bioline TB Ag MPT64 and niacin paper strip BD . Used diagnostic test 2x2 to analyze sensitivity, specificity, negative predictive value and positive predictive value. Ziehl-Neelsen staining microscopy Sensitivity 83,33 %  and Specificity 95,65% of  , PPV  90,91%and NPV 91,67%, Diagnostic Accuracy 91,43 % . Xpert MTB/RIF Sensitivity 75% and Specificity 95,65% , PPV  90 % and NPV 88 %, Diagnostic Accuracy 88,57 % with 95% CI (Confidence Interval ) . Characteristics female dominated 23/35 (65.7%) while Male numbered 12/35 (34.3%), age range distribution of TB lymphadenitis patients is highest in young adults 17 years to 25 years as many as 15/35 (42.9%) the second highest is the age group of 36 years to 45 years by 8/35 (22.9%), Clinicial presentation are mostly lymph node enlargement in cervical  37% patients other locations supraclavicular ,mamae. Clinical symptoms mostly lymphadenopathy 31,5% and other lymphadenopathy with fever. Microscopy method still have the good validity shoul be conjunction with the  molecular rapid tests and culture as gold standard in determining the diagnosis of TB lymphadenitis.